2014
DOI: 10.1016/j.bspc.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between robotic technology and health care

Abstract: Although technology and computation power have become more and more present in our daily lives, we have yet to see the same tendency in robotics applied to health care. In this work we focused on the study of four distinct applications of robotic technology to health care, named Robotic Assisted Surgery, Robotics in Rehabilitation, Prosthetics and Companion Robotic Systems. We identified the main roadblocks that are limiting the progress of such applications by an extensive examination of recent reports. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 100 publications
0
34
0
4
Order By: Relevance
“…Karel Capek, introdujo el término "Robot" por primera vez en 1921, en una obra teatral denominada Rossum's universal Robots (en español: "los robots universales de Rossum"). Donde describió máquinas inteligentes que aunque se crearon para servir a los humanos, dominaban el mundo y destruían la humanidad 37 . Desde ese entonces hasta el presente, esa idea ha evolucionado bastante y vemos el gran avance en la concepción e implementación de la robótica, como lo es en terapias de rehabilitación.…”
Section: Marco Teórico La Robóticaunclassified
“…Karel Capek, introdujo el término "Robot" por primera vez en 1921, en una obra teatral denominada Rossum's universal Robots (en español: "los robots universales de Rossum"). Donde describió máquinas inteligentes que aunque se crearon para servir a los humanos, dominaban el mundo y destruían la humanidad 37 . Desde ese entonces hasta el presente, esa idea ha evolucionado bastante y vemos el gran avance en la concepción e implementación de la robótica, como lo es en terapias de rehabilitación.…”
Section: Marco Teórico La Robóticaunclassified
“…Its natural form is defined as the total kinetic energy, T, of the system minus its total potential energy, V, [4][5][6] as shown in equation (3). The total kinetic energy, which is the sum of both linear, T E and rotational, T R kinetic energy, can be derived using the formula shown in equation (4), whilst the equation for the total potential energy, V is shown in equation (5).…”
Section: Deriving and Solving 2-dof Dynamic Equationmentioning
confidence: 99%
“…Usually, these physiotherapy training sessions are considered labor-intensive and the training duration is usually limited either by personnel shortages or therapist fatigue during the sessions [4][5]. These indirectly affect the sessions to become shorter than required to gain an optimal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The training results showed that it greatly assisted with the treatment. The research team led by Loureiro, et al [10,11] developed an upper limb rehabilitation training robot that it could provide passive training, active training and impedance training. Clinical trials showed that it strongly influenced the rehabilitation of the upper limb.…”
Section: Introductionmentioning
confidence: 99%